Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Siswa dalam Pembelajaran Tematik Terpadu di Kelas V SD - Handayani, Roza Humaira; Muhammadi, Muhammadi (Universitas Negeri Padang, 2021)
This research aims to know The influence of Problem Based Learning model towards students’ learning achievement on Integrated Thematic Learning At The Grade V of SDN cluster 4 in Padang Timur sub – district, Padang. The type of research used was quasi experiment design. The design used in the research was Non – equivalent Control Group Design. The sample was taken by cluster random sampling . The population of the research was all five years students of SDN cluster 4 in Padang Timur sub – district, Padang which consists of 10 schools. The instruments used in the research was writing test in the form of an objective test. Data analysis technique Used in the research was t-test with acquisition = 4,34 > ttabel= 2,037, with a real level 0,05 which means H1 was received and Ho was rejected. In conclusion , the implementation Problem Based Learning model had significant effect on students learning achievement on Integrated Thematic Learning At The Grade V of SDN 35 Parak Karakah in Padang Timur sub – district, Padang.